ANALISIS FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL: (Studi pada Perusahaan Manufaktur Sektor Miscellaneous Industry yang Terdaftar di Bursa Efek Indonesia (BEI) periode 2014-2019) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
The company capital structure in implementing funding decisions that result in capital uses funds from internal and external sources of the company. The company external funds come from debt while internal funds come from the equity side such as retained earnings, own capital, common stock and preferred stock. Several factors are considered capable of influencing the capital structure such as: profitability, sales growth, asset structure, and non-debt tax shield. This study aims to analyze the effect of profitability, sales growth, asset structure, and non-debt tax shield on the capital structure of manufacturing companies in the Miscellaneous Industry sector listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period. This type of research uses quantitative research that uses numerical data or numbers. The research object used in this study is the Miscellaneous Industry which was listed on the Indonesia Stock Exchange (IDX) in 2014-2019, which amounted to 18 companies. The type of data used in this study is the type of secondary data with the method of documentation. The results of the research data test showed that: 1) Testing the first hypothesis of the study found no effect of profitability (X1) on the company capital structure. 2) Testing the second hypothesis of the study obtained a significance smaller than the level of a = 5%. So it can be decided that in accordance with the research hypothesis, the asset structure (X2) has an influence on the company capital structure. 3) Testing the third hypothesis in this study obtained a significance level smaller than a = 5%. So it can be decided that sales growth (X3) has an influence on the company capital structure. 4) Testing the fourth hypothesis of this study obtained a significance level greater than a = 5%. So it can be decided that the non-debt tax shield (X4) has no effect on changes in the company capital structure.
Keywords: Capital Structure; Profitability; Sales Growth; Asset Structure; and Non-Debt Tax Shield